Lee In the Shadow of Washington - McCaslin, Richard B. (Book collections on Project MUSE., 2001)
While most scholars agree that Robert E. Lee's loyalty to Virginia was the key factor in his decision to join the Confederate cause, Richard McCaslin goes further to demonstrate that Lee's true call to action was the legacy of the American Revolution viewed through his reverence for George Washington. Like Washington, Lee wore a colonel's uniform. He rode a horse named for one of his idol's mounts, Traveller, and carried one of Washington's swords. On January 19, 1861, his fifty-fourth birthday, Lee sat alone in his room at Fort Mason and faced the prospect of war by reading the latest book ab.